Effects of Lisdexamfetamine, a Prodrug of D-Amphetamine, on Locomotion, Spatial Cognitive Processing and Neurochemical Profiles in Rats: A Comparison With Immediate-Release Amphetamine - Jian-min, Chen; Zhi-yuan, Wang; Shi-xuan, Wu; Rui, Song; Ning, Wu; Jin, Li (Frontiers in Psychiatry, 2022)
D-amphetamine has been used to enhance cognitive performance over the last few decades. Due to the rapid absorption after administration, d-amphetamine shows narrow effective window and severe abuse potential. Lisdexamfetamine, a prodrug of d-amphetamine, reduces the magnitude of plasma d-amphetamine concentration and prolongs the action duration when compared with immediate-release d-amphetamine at equimolar doses. However, the differences of these two drugs, which produce distinct pharmacokinetic characteristics, in cognition improvement still unclear. In present study, we compared the effects of d-amphetamine (i.p) and lisdexamfetamine (p.o) at equimolar doses (0.2, 0.5, 1.5, 4.5, and 13.5 mg/kg of d-amphetamine base) on locomotion, spatial working memory and recognition memory in rats. Given the crucial involvement of dopamine neurotransmitter system within the medial prefrontal cortex (mPFC) in cognitive processing, microdialysis was conducted to profile the difference in neurochemical characteristics between the two drugs. In our results, d-amphetamine ranges from 0.5 to 1.5 mg/kg significantly increased locomotor activity. However, d-amphetamine ranges from 0.2 to 13.5 mg/kg failed to improve spatial working memory and recognition memory in Y-maze-based spontaneous alternation and two-trial delayed alternation tasks of rats, respectively. In contrast, lisdexamfetamine with 4.5 mg/kg significantly increased the locomotion and improved both spatial working and recognition memory. Further, microdialysis showed that lisdexamfetamine induced lower magnitude and longer duration of extracellular dopamine increase than that of d-amphetamine. These results suggest that lisdexamfetamine was more effective than d-amphetamine in improving spatial cognitive performance, which was attributed to the steady and lasting dopamine release pattern within the mPFC.